Marxism and the Methodologies of History - Pierson, Stuart (Labour / Le Travail, 1985)
This article reviews the book, "Marxism and the Methodologies of History," by Gregor McLennan.
Keywords: LES syndicates britanniques sous les gouvernments travaillistes (Book); Nonfiction; RAVIER; Jean-Pierre; REVIEWS; books